Delicious. Series 3 [videorecording (DVD)] - French, Dawn; Glen, Iain, 1961-; Fox, Emilia, 1974-; Reynolds, Tanya; Nero, Franco; Hancock, Sheila, 1933- (Acorn Media, 2019)
It's been almost a year since the sudden death of philandering chef Leo Vincent, but his presence at the Penrose Hotel is more palpable than ever. His ex-wife, Gina, and widow, Sam, have the business, but they continue to have professional and personal disagreements.